Validation of an assessment tool for professionalism in medical students: a mixed method study - Khan, Humaira Fayyaz; Yasmeen, Raheela; Ali, Shabana (Journal of the Pakistan Medical Association, 2023)
Objective: To develop and validate a tool for the assessment of professionalism in medical students during clerkship. Method: The mixed-method study was confucted from February to September 2018 at the Islamic International Medical College, Riphah University, Islamabad, Pakistan. A preliminary focus group discussion ws followed by two rounds of Delphi technique to validate micro-scenarios for the relevance of each item of the instrument alongside its content validity. For content and construct validation of the tool, content validity, cognitive validity, cognitive pretesting, confirmatory factor analysis and reliability assessment was done. Piloting was done on medical students doing clerkship. Data was analysed using SPSS 21 and AMOS 21. Results: A 35-item preliminary tool from micro-scenarios generated after focus group discussion was developed for the first Delphi round. For the second round, a 29-item tool was resent to the experts for validation. After the second round, the content validity scale was 0.94. Removal of 1 item produced a 28-item tool. Pre-cognitive testing of the 28 items resulted in rephrasing of 4, modification of 2, and deletion of 1 and a tool with 27 items. Piloting was carried out and after CFA resulted in a reduced 21 item tool. Cronbach’s alpha value was 0.96. A good to excellent model fit was produced after performing confirmatory factor analysis. Conclusion: A tool comprising of 21 items scored on a 5-point Likert scale that had acceptable construct validity and good content validity was developed. It can be used to evaluate the level of professionalism of local medical students doing clerkship. Key Words: Professionalism, Delphi, Focus group, Medical students, Factor analysis.